The effects of nutritional status, parenting styles, and self-confidence on the motor skills of elementary school karate participants - Windy Nelsya Camella; Tjung Hauw Sin; Gusril Gusril; Andri Gemaini (Journal of Educational and Learning Studies, 2026)
This study aimed to examine the direct and indirect effects of nutritional status, parenting styles, and self-confidence on the motor skills of elementary school karate participants. A quantitative cross-sectional design was employed involving 59 male karate participants aged 9–11 years selected through purposive sampling. Nutritional status was assessed using body mass index, while parenting styles, self-confidence, and motor skills were measured using validated questionnaires and the Scott Motor Ability Test. Data were analyzed using path analysis after normality and linearity assumptions were confirmed. Nutritional status, parenting styles, and self-confidence significantly affected motor skills both directly and indirectly (p < 0.05). Parenting styles showed the strongest direct effect (37.09%), followed by nutritional status (33.52%) and self-confidence (27.56%). The structural model explained 72.3% of the variance in motor skills. Motor skills among elementary school karate participants are jointly influenced by biological, family, and psychological factors, highlighting the importance of integrating nutritional improvement, supportive parenting, and confidence-building strategies to optimize children's motor development.